2D Metal Chalcogenides for IR Photodetection. Issue 30 (21st May 2019) - Wang, Fakun; Zhang, Yue; Gao, Yu; Luo, Peng; Su, Jianwei; Han, Wei; Liu, Kailang; Li, Huiqiao; Zhai, Tianyou
Abstract: Infrared (IR) photodetectors are finding diverse applications in imaging, information communication, military, etc. 2D metal chalcogenides (2DMCs) have attracted increasing interest in view of their unique structures and extraordinary physical properties. They have demonstrated outstanding IR detection performance including high responsivity and detectivity, high on/off ratio, fast response rate, stable room temperature operability, and good mechanical flexibility, which has opened up a new prospect in next‐generation IR photodetectors. This Review presents a comprehensive summary of recent progress in advanced IR photodetectors based on 2DMCs. The rationale of the photodetectors containing photocurrent generation mechanisms and performance parameters are briefly introduced. The device performances of 2DMCs‐based IR photodetectors are also systematically summarized, and some representative achievements are highlighted as well. Finally, conclusions and outlooks are delivered as a guideline for this thriving field. Abstract : The booming development of 2D metal chalcogenides has received tremendous attention. In this Review, the recent progress of state‐of‐the‐art infrared photodetectors based on 2D metal chalcogenides is comprehensively summarized.